The Relevance of Islamic and Customary Law on Concerning of Domestic Violence in Bali's Case Study (Research, Society and Development, 2020)
This study aims to determine the relevance of Islamic and customary law in Bali with acts of domestic violence, which are related to Law No. 23/2004. This research is a qualitative study with a normative juridical approach, through literature studies and exploration methods from secondary data. The objects examined in this study are Balinese Customary Law, Islamic Law, and Law No. 23/2004 concerning the Elimination of Domestic Violence. The case object in this study originated from several cases of domestic violence in Bali. The results of the study showed that domestic violence increased every year, where the majority of victims were women. Several factors cause cases to occur, where the Balinese tradition with the patrilineal system is an important factor that creates a gap between men and women. Referring to Islamic and customary law in Bali does not explicitly explain the rules and sanctions related to internal violence. However, this local regulation still does not justify the existence of acts of violence in the household by applicable law.